Analysis of factors affecting the incidence of hypertension in the productive age group at the Muara Beliti community health center: A cross-sectional study - Indrasari, Mislia; Harokan, Ali; Suryani, Lilis (STIKes Al-Ma'arif Baturaja, 2025)
Background Hypertension is one of the leading non-communicable diseases with increasing prevalence, including among the productive age group. Several risk factors such as age, occupation, body weight, family history, smoking habits, physical activity, and fruit and vegetable consumption are suspected to influence the incidence of hypertension. Objective This study aimed to analyze the factors affecting the incidence of hypertension among productive age individuals in the working area of Muara Beliti Public Health Center in 2025. Methods This was a quantitative study using a cross-sectional approach. A total of 93 respondents aged 16–64 years were selected using purposive sampling. Data were collected through questionnaires and medical records, then analyzed using Chi-Square and multivariate logistic regression tests. Results The results showed significant relationships between age (p=0.031), body weight (p=0.001), smoking habits (p=0.030), physical activity (p=0.016), and fruit and vegetable consumption (p=0.011) with the incidence of hypertension. No significant relationship was found between occupation and family history with hypertension. Multivariate analysis revealed that physical activity was the most dominant factor (p=0.002; OR=4.80; 95% CI=1.80–12.80). Conclusion Physical activity is the most dominant factor influencing the incidence of hypertension among the productive age population.Health interventions should prioritize increasing physical activity, promoting healthy eating habits, and controlling other risk factors to reduce the incidence of hypertension among productive age individuals.